Peran Disiplin Kerja Terhadap Kinerja Karyawan Kantor Dinas Perhubungan di Kabupaten Lampung Tengah - Rany Sitara Dewi; Sungkono; Maman Mulya Karnama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Employee performance is not as expected, this is because there are employees of the Central Lampung Regency Transportation Service who, while working, are not able to comply with regulations in a disciplined manner. This study aims to analyze work discipline on employee performance. Causal associative approach with quantitative research is the type of research used in this study. The sampling technique used was total sampling with a total of 30 employees who were used as the population and sample in this study. The types of data used in this study are primary data through questionnaires and secondary data from employee attendance and performance reviews. Methods of data collection using a questionnaire. The data analysis technique is by testing requirements analysis and also testing hypotheses with simple linear regression analysis techniques and determinant coefficients with the help of SPPS 20.00. The results showed that work discipline in the good category (50%), employee performance in the high category (63.33%.). Simple linear regression test of 12.494 significant value sig 0.007 <0.05. R square value 0.229. 22.9% work discipline can affect employee performance and the remaining 77.1% that affect employee performance are other factors. The t value is 007 with a significant value of 0.007<0.05 so that there is a significant effect between the two variables. Testing the regression coefficient value of 0.585 with a significant value of 0.007 <0.05 where each work discipline unit can increase 0.585 employee performance units. So, work discipline affects employee performance.